Retrograde intrarenal surgery in the management of solitary large renal stones, 2-3 cm: a single center experience - Eissa, Ahmed; Ragab, Maged; Bianchi, Giampoalo; Hassan, Ayman (International Surgery Journal, 2021)
Background: Nephrolithiasis represents a major health burden worldwide. Several treatment options are available for renal stones such as open stone surgery, percutaneous nephrolithotomy (PCNL), retrograde intrarenal surgery (RIRS), and extracorporeal shockwave lithotripsy. PCNL is considered the gold standard treatment for large renal stones (>2 cm); however, it is associated with higher blood loss, complication rates, and longer hospitalization. In this setting, we aimed to assess the value of RIRS in the management of single large renal stones between 2-3 cm. Methods: The database of our center was reviewed to include all the patients who underwent RIRS for single large renal stone (2-3 cm) between February 2018 and April 2019. All the patients were evaluated by preoperative computed tomography to evaluate the stone size, site, and density. Furthermore, the following variables were also collected; pre- and post-operative hemoglobin and creatinine, the operative time, stone free rate (SFR), and duration of hospital stay. All the statistical analysis was performed using SPSS version 20. Results: Overall, the data of 31 patients were retrieved for the current study. The mean age of the patients was 56.9±12.9 years, and the mean stone size was 22.6±7 mm. The mean operative time was 96.4±37.3 minutes and the SFR was 74.2% after single session of RIRS. No major postoperative complications were reported in the current series. Conclusions: RIRS is a safe and efficient alternative to PCNL in the management of single renal stones between 2-3 cm; however, further prospective studies are required to confirm these findings.